Widespread white matter changes in post-H1N1 patients with narcolepsy type 1 and first-degree relatives. Issue 10 (17th July 2018) - Juvodden, Hilde T; Alnæs, Dag; Lund, Martina J; Agartz, Ingrid; Andreassen, Ole A; Dietrichs, Espen; Thorsby, Per M; Westlye, Lars T; Knudsen, Stine
Abstract: Study Objectives: To assess white matter involvement in H1N1-vaccinated hypocretin deficient patients with narcolepsy type 1 (NT1) compared with first-degree relatives (a potential risk group) and healthy controls. Methods: We compared four diffusion tensor imaging–based microstructural indices (fractional anisotropy [FA], mean diffusivity [MD], radial diffusivity [RD], and axial diffusivity [AD]) in 57 patients with NT1 (39 females, mean age 21.8 years, 51/57 H1N1-vaccinated, 57/57 HLA-DQB1*06:02 -positive, 54/54 hypocretin-deficient), 54 first-degree relatives (29 females, mean age 19.1 years, 37/54 H1N1-vaccinated, 32/54 HLA-DQB1*06:02 -positive), and 55 healthy controls (38 females, mean age 22.3 years). We tested for differences between these groups, for parametric effects (controls > first-degree relatives > patients) and associations in patients (cerebrospinal fluid [CSF] hypocretin-1 and disease duration) and first-degree relatives ( HLA-DQB1*06:02 and H1N1-vaccination). We employed tract-based spatial statistics and used permutation testing and threshold-free cluster enhancement for inference. Results: Patients with NT1 had a widespread, bilateral pattern of significantly lower FA compared with first-degree relatives and healthy controls. Additionally, patients with NT1 also exhibited significantly higher RD and lower AD in several focal white matter clusters. The parametric model showed that first-degree relatives had intermediate values. Full sample of patients with NT1 showed no significant associations with disease duration or CSF hypocretin-1. Conclusions: Our study suggests widespread abnormal white matter involvement far beyond the already known focal hypothalamic pathology in NT1, possibly reflecting the combined effects of the loss of the widely projecting hypothalamic hypocretin neurons, and/or secondary effects of wake/sleep dysregulation. These findings demonstrate the importance of white matter pathology in NT1.